Sequência didática baseada na energia solar fotovoltaica como auxílio ao ensino de física no 3º ano do ensino médio - Cruz, Alê de Souza (2019)
A current problem for the teacher working in science is the lack of motivation of students facing current teaching methods, where many schools, even in very traditional schools have been changing their approaches with practical classes, construction of laboratories both science as of robotics. These changes can be noticed with greater intensity in private schools (CASTRO, 2015). But what do we do to change the current panorama of our public schools? This is one of the initiatives of this work that comes to assist the teacher of the Third Year of High School in the experimental area, making use of new technologies such as photovoltaic solar energy to work subjects within the area of electricity. Taking into consideration the environmental area and the incentive to use renewable energy. With this kind of activity we can encourage the elementary school student to explore other ways of producing electricity by taking advantage of what is abundant in our region that is solar energy. Taking into account the previous knowledge of the student to have a more meaningful learning.